PERAN PENYULUH PERTANIAN LAPANGAN PADA KELOMPOK TANI DALAM MENGEMBANGKAN KOMODITI TANAMAN PANGAN - Zainol Arifin; Anis Trianawati; Titik Musriati Musriati (BUANA SAINS, 2022)
The agricultural instructor is a party that assists farmers in developing farming. Agricultural instructors must act as facilitators, communicators, and motivators to encourage farmers to participate in facilitating the progress of their farming business. The aim of this study was to determine the role of field agricultural extension workers in farmer groups in developing food crop commodities in Kolilanang Village, Adonara District, East Flores Regency. The method used a descriptive qualitative with a Likert Scale. The results showed that the role of extension workers as facilitators in this study obtained a total score of 399 or 88.6%. For the role of the Agricultural instructors as a communicator, a total score of 398 or 88.4% was obtained, while for the role of the Agricultural instructors as a motivator, a score of 394 or 87.5% was obtained. The role of Agricultural instructors as facilitators, motivators, and communicators in farmer groups in Kolilanang Village, Adonara District, East Flores Regency is categorized as very good or farmers get support in developing agriculture, especially in food agriculture.